PENGARUH PARTISIPASI ANGGARAN TERHADAP KINERJA MANAJERIAL DENGAN PENGETAHUAN MANAJEMEN BIAYA DAN BUDAYA ORGANISASI SEBAGAI VARIABEL PEMODERASI - Nevita, Ade Octa Nevita Octa; Farida, Dessy Noor; Imaningati, Sri (PRESTASI, 2014)
ABSTRACTÂ This study aimed to examine the effect of budgetary participation and managerial performance. Contingency approach used in this study because there are espects of each situation in the implementation of relationship budgetary participation on managerial performance. Know ledge management and organizational culture cost is a factor that is used to moderate the relationship. This research was carried out to managers in Jepara furniture company by distribusting questionaires distributed directly as a method of data collection. Based on data Analysis, proving that positive effect of budget participation on manajerial performance. Result of the interaction of knowledge management can strengthen the relationship participation fee budget and managerial performance. Entirely shown by the results of the significance value is less than 0.05. Results interactions weaken the organiztional culture of participation and managerial performance relationship. Significant results are indicated by values greater than 0.05. Â Keywords : Budget Participation, Managerial Performance, Cost Management Knowledge, Organizational Culture.Â